A simple chemical method of opening and filling carbon nanotubes - Tsang, S; Chen, Y; Harris, P; Green, M (Macmillan Magazines Ltd, 1994)
Since carbon nanotubes were first synthesized in macroscopic quantities, it has become possible to explore their physical and chemical characteristics. There has been much speculation about the properties of materials encapsulated within the tubes, but experimental studies of this issue require a reliable means of opening and filling the tubes. Various approaches have been developed for opening up the tube ends and encapsulating material, but these work only for a limited range of materials or in low yield. Here we describe a general method that allows carbon nanotubes to be opened at the end and filled with a variety of metal oxides using wet chemical techniques. We anticipate that this method will lead to extensive study of the chemistry and physics of filled nanotubes, which might find applications in catalysis, separation and storage technology and in the development of materials with new magnetic and electrical properties.